1999
DOI: 10.1530/eje.0.1410350
|View full text |Cite
|
Sign up to set email alerts
|

Population based study on serum ionised calcium, serum parathyroid hormone, and blood pressure. The Tromso study

Abstract: Objective: To study associations between serum ionised calcium, serum parathyroid hormone (PTH) and blood pressure. Design: A population based, cross-sectional study was used. Methods: Blood pressure, body mass index, serum ionised calcium and serum PTH were measured in 460 males and 486 females in the Tromsø study in 1994/1995. None were on medication for hypertension. The data were analysed with a multiple linear regression model. Results: When looking at subjects with serum ionised calcium <1.39 mmol/l, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
56
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(64 citation statements)
references
References 38 publications
6
56
2
Order By: Relevance
“…However, they did not adjust for serum calcium, and in the multivariate analysis age lost its significance as an explanatory variable for PTH. In our study, age was the most significant explanatory variable for serum PTH, which is in accordance with another population-based epidemiological study (19). Lind et al (18) studied 143 hypertensive and 51 normotensive subjects and measured serum PTH in a random subgroup of 76 subjects.…”
Section: Discussionsupporting
confidence: 91%
“…However, they did not adjust for serum calcium, and in the multivariate analysis age lost its significance as an explanatory variable for PTH. In our study, age was the most significant explanatory variable for serum PTH, which is in accordance with another population-based epidemiological study (19). Lind et al (18) studied 143 hypertensive and 51 normotensive subjects and measured serum PTH in a random subgroup of 76 subjects.…”
Section: Discussionsupporting
confidence: 91%
“…Cases with mild pHPT also have an increased risk of morbidity and mortality of the cardiovascular system (3,(33)(34)(35). Several populationbased studies and investigations with patients recruited consecutively have confirmed the association between pHPT and cardiovascular diseases, where both calcium and PTH are associated directly or indirectly with increased morbidity and mortality (2,(36)(37)(38). Moreover, in population-based studies, calcium per se, in the normal range without associated disturbances in serum PTH, also has a positive association with hard endpoints such as myocardial infarction (39,40).…”
Section: Discussionmentioning
confidence: 98%
“…9 All men and women older than 29 years, living in the municipality of Tromsø and that participated in the second phase of the fourth Tromsø study 10 or became 30, 40, 45, 60 or 75 years old during 2001, were invited to participate. All subjects filled in a health questionnaire including smoking status, use of thyroxine and blood pressure lowering medication.…”
Section: Methodsmentioning
confidence: 99%
“…Height, weight and blood pressure were measured as described previously. 10 Body mass index (BMI) was calculated as weight (kg) divided by squared height (m 2 ). Non-fasting blood samples were drawn between 0800 and 1600 h, and analyzed for serum TSH as described previously (reference range 0.20-4.00 mIU/l).…”
Section: Methodsmentioning
confidence: 99%